Development and Dynamics of Cytomegalovirus UL97 Ganciclovir Resistance Mutations in Transplant Recipients Detected by Next-Generation Sequencing. (4th September 2021) - Lodding, Isabelle P; Jørgensen, Mette; Bennedbæk, Marc; Kirkby, Nikolai; Naegele, Klaudia; Gustafsson, Finn; Perch, Michael; Rasmussen, Allan; Sengeløv, Henrik; Sørensen, Søren S; Hirsch, Hans H; Lundgren, Jens D
Abstract: Background: (Val)ganciclovir resistance mutations in CMV UL97 (UL97-GCV-R) complicate anti-CMV therapy in recipients of solid organ and hematopoietic stem cell transplants, but comprehensive data on prevalence, emergence, and outcome are scarce. Methods: Using next-generation sequencing (NGS; Illumina MiSeq platform), we analyzed UL97-GCV-R in patients with available plasma samples and refractory CMV replication/DNAemia (n = 87) containing viral loads ≥910 IU/mL. Twenty-one patients with CMV DNAemia resolving under antiviral therapy were analyzed as controls. Detected mutations were considered induced and of potential clinical significance if they increased by ≥10% compared with the first detected frequency or if they had a maximum frequency ≥25%. Results: Nineteen of 87 (21.8%) with refractory CMV replication had ≥1 UL97-GCV-R detected by NGS, in comparison to 0/21 of the controls ( P = .02). One-third of the recipients had 2 or more induced UL97-GCV-R mutations. The most frequently induced mutations affected codons 595 (42% [8/19]), 594 (32% [6/19]), and 603 (32% [6/19]). C592G was present in all episodes of both cases and controls at frequencies <15%, but never induced. UL97-GCV-R tended to be more frequent in donor/recipient CMV immunoglobulin G mismatch or following failure to complete primary prophylaxis, and many developed invasive CMV disease. Conclusions: UL97-GCV-R is common among transplant patients with refractory CMV replication. Early testing by NGS allows for identification of major mutations at codons 595, 594, and 603 and excludes a major role of C592G in ganciclovir resistance. Large prospective studies on UL97-GCV-R are warranted.